INTRODUCTION OF NEW SKILL «IN-SERVICE TRAINER» IN WORLDSKILLS RUSSIA - Vitaly A. Kopnov; Anna V. Sokolova (Russian State Vocational Pedagogical University, 2015)
The aim of the study is to find out new and effective teaching tools and technologies that enhance the training level of in-service trainers. As one of these tools, the development of competitive movement is offered, which actively engages students into the professional work.Methods. The comprehensive assessment of the scope of secondary vocational education and training (VET) and comparative analysis of professional skills contests in Russian regions with the aim to identify existing organizational and competitive challenges are provided.Results. On the basis of these studies, the positive effect of training of in-service trainers on the use of professional skills contests is outlined.Scientific novelty. Integration of in-service training at all levels of training - from students to experienced workers into receivership motion would allow us to create a creative learning environment, promoting active self-development group of training of vocational trainers in general.Practical significance. The research results can be useful to teachers of secondary and postsecondary VET institutions in the further study of the organizational and creative foundations of training of in-service trainers.